Power development planning with demand side management : residential lighting in the rural areas of Thailand - Prasertsak Cherngchawano; Shrestha, Ram M.; Surapong Chiraratananon; Chen, Xavier; Electricity Generating Authority of Thailand (EGAT) (Bangkok : Asian Institute of Technology, 1994)
This study deals with the electricity expansion planning with demand-side management for the integrated electric system of Thailand. The demand-side option chosen is the use of efficient lighting appliances in household sector. Residential lighting load shape is modeled based on customer behavior. The Load forecast from the Thailand Load Forecast Subcommittee is used as Base Case. And Load Model of the Westinghouse Interactive Generation Planning (LM of WIGPLAN) is used for load duration curves forecasting. Wien Automatic System Planning Package (WASP) is used for expansion planning. The survey in the selected rural area of Thailand is conducted for analysis of lighting load shapes. The resulting expansion plan suggested that demand-side management options like use of both efficient fluorescent lamp and ballast could be implemented in household sector of Thailand by 25% of the total provincial customers to reduce system peak load. The peak load reduction can be achieved as the same amounts as from the replacement of all traditional fluorescent lamps with efficient fluorescent lamps. The replacement of all traditional ballast will pass the societal perspective test if the efficient ballast is produced in Thailand with cost lower than the present cost. Most of the residential customers consume electricity less than 150 kWh per month. The low electricity tariff of that consumption level is not interesting in customer perspective. The utility should purchase bulk volume of efficient lighting appliances and make cost recovery through the Automatic Price Mechanism. It was found that demand-side management could sometime increase the energy cost in the high fuel intensive industry as Thai electric system. But the economy of scale from large plant can be achieved even though the share of capital cost is only 20%.
A thesis submitted m partial fulfillment of the requirement for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 1994
Keywords: Lighting -- Thailand